Learning Assessment in Kurikulum Merdeka: Practice and Challanges in EFL Classroom - Rama Dwika Herdiawan; Eva Fitriani Syarifah; Fathan Ghotafani; Azman, Mohamed Nor Azhari (Papanda Journal of English Education, 2023)
Assessment is considered important for improving students’ performance and contributing to better teaching and more efficient learning. This research aims to explore how EFL teacher implement the learning assessment in the class, and the challenges faced by teacher in conducting the assessment. Thus, this research was conducted at one of vocational schools in Majalengka. This research employs a narrative inquiry as the research design. This research use observation, document analysis and interview as the data collection method. The observation was conducted two times at eleventh-grade class and the interview was delivered to an English teacher. The researcher analyzed the teacher document, to determine whether they comply with the guidelines of the Kurikulum Merdeka. The research reveals that the teacher effectively implements formative and summative assessments in line with government guidelines. Formative assessments occur during group discussions with ongoing feedback, while summative assessments involve group presentations at the end of a unit to evaluate students' comprehension of report texts. These assessments incorporate Profil Pelajar Pancasila values, namely collaboration and creativity. The assessments adhere to principles of language assessment, including practicality, reliability, validity, authenticity, and positive washback. Practicality is seen in manageable tasks, reliability in clear scoring rubrics, validity in content alignment with learning objectives, authenticity in real-world language use, and washback in motivating students and boosting their confidence. The limited class time poses a challenge, making it difficult for the teacher to provide detailed feedback.